Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To transform the quadratic equation [tex]\(y = (2x + 3)^2\)[/tex] into its standard form, we need to expand the expression [tex]\((2x + 3)^2\)[/tex].
Here are the steps to do this:
1. Start with the given equation:
[tex]\[ y = (2x + 3)^2 \][/tex]
2. To expand [tex]\((2x + 3)^2\)[/tex], use the binomial theorem [tex]\((a + b)^2 = a^2 + 2ab + b^2\)[/tex], where [tex]\(a = 2x\)[/tex] and [tex]\(b = 3\)[/tex].
3. Apply the binomial theorem:
[tex]\[ (2x + 3)^2 = (2x)^2 + 2 \cdot (2x) \cdot 3 + 3^2 \][/tex]
4. Calculate each term:
[tex]\[ (2x)^2 = 4x^2 \][/tex]
[tex]\[ 2 \cdot (2x) \cdot 3 = 12x \][/tex]
[tex]\[ 3^2 = 9 \][/tex]
5. Combine all the terms:
[tex]\[ (2x + 3)^2 = 4x^2 + 12x + 9 \][/tex]
6. Set [tex]\(y = (2x + 3)^2\)[/tex] to [tex]\(0\)[/tex] to find the standard form of the quadratic equation:
[tex]\[ y = 4x^2 + 12x + 9 \][/tex]
Therefore, the standard form of the given quadratic equation is:
[tex]\[ 0 = 4x^2 + 12x + 9 \][/tex]
So, the correct choice is:
[tex]\[ 0 = 4 x^2 + 12 x + 9 \][/tex]
Here are the steps to do this:
1. Start with the given equation:
[tex]\[ y = (2x + 3)^2 \][/tex]
2. To expand [tex]\((2x + 3)^2\)[/tex], use the binomial theorem [tex]\((a + b)^2 = a^2 + 2ab + b^2\)[/tex], where [tex]\(a = 2x\)[/tex] and [tex]\(b = 3\)[/tex].
3. Apply the binomial theorem:
[tex]\[ (2x + 3)^2 = (2x)^2 + 2 \cdot (2x) \cdot 3 + 3^2 \][/tex]
4. Calculate each term:
[tex]\[ (2x)^2 = 4x^2 \][/tex]
[tex]\[ 2 \cdot (2x) \cdot 3 = 12x \][/tex]
[tex]\[ 3^2 = 9 \][/tex]
5. Combine all the terms:
[tex]\[ (2x + 3)^2 = 4x^2 + 12x + 9 \][/tex]
6. Set [tex]\(y = (2x + 3)^2\)[/tex] to [tex]\(0\)[/tex] to find the standard form of the quadratic equation:
[tex]\[ y = 4x^2 + 12x + 9 \][/tex]
Therefore, the standard form of the given quadratic equation is:
[tex]\[ 0 = 4x^2 + 12x + 9 \][/tex]
So, the correct choice is:
[tex]\[ 0 = 4 x^2 + 12 x + 9 \][/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.